Who should pick up the bill? Distributing the financial burden of technological innovations in schools. (March 2016) - Hassan, Mamdouh; Geys, Benny
Abstract: Technological innovations in classrooms generally come with substantial financial price tags. Although the distribution of such financial costs is of critical importance to practitioners, (potential) users, and policy-makers, little is known about different stakeholders' preferences towards who should pick up this bill. In this article, we exploit information obtained from a unique survey in Flanders (Belgium) to help fill this research gap. We thereby particularly assess how financing preferences depend on stakeholders' role in the educational environment (i.e. public officials, school principals, teachers, ICT administrators and parents) and their knowledge about the true extent of technological innovations' financial cost. Our main findings indicate that all stakeholders included in our analysis prefer to shift the financial burden of technological innovations at least to some extent onto other stakeholders. Yet, explicitly informing respondents about the high and diverse financial costs of tablets in schools tends to shift preferences towards funding models representing more equitable distributions of the financial burden. Highlights: We analyze preferences towards the distribution of the financial burden of integrating ICTs in school environments. We study results from a unique survey in Flanders (Belgium). We find that financing preferences depend on stakeholders' role in the educational environment. We show that financing preferences depend on knowledge about ICTs' total financial cost.